Integrasi Anggaran Laba Rugi dan Neraca dalam Struktur Master Budget: Analisis Komparatif Perusahaan Dagang, Jasa, dan Manufaktur - Fitri Aulia; Grace Aurelia Girsang; Kevin Adrigo Siahaan (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study analyzes the integration of income statement and balance sheet budgets within the master budget framework across trading, service, and manufacturing companies. Using a qualitative literature review of ten scientific articles (2020–2026), the findings show that the income statement budget projects operational performance, while the budgeted balance sheet projects financial position. Both budgets integrate through net income, which increases retained earnings. Manufacturing companies require the most complex synchronization due to production cycles and multi-tiered inventory. In contrast, service and trading companies focus on operational efficiency and liquidity management. Budgeting steps differ significantly across sectors, particularly in inventory treatment, cost of goods sold, and operating expense allocation. Integration success depends on accurate sales forecasting, cash budgeting, and consistent accounting standards.